PENGARUH PENGGUNAAN TEPUNG DAUN KELOR SEBAGAI BAHANPENSUBTITUSI TEPUNG TAPIOKA TERHADAP TINGKATKEKENYALAN DAN DAYA TERIMA CILOK - Aulia Khusna, Dita, Rusdin Rauf, S.TP., M.P, Fitriana Mustikaningrum, S.Gz, M.Sc (2015)
Introduction : The less of calcium consumption gives negative effect of growing process especially in the teenager who has grown process growth spurt is the growing level of height (peak high velocity) and weight (peak weight velocity). The kelor leaf flour has high calcium, there is 200 mg/ 100 g. The kelor leaf flour has a potency as the substitution ingredients of tapioca flour in the process of making cilok to increase nutrition in cilok itself. Objective : To know the influence of using kelor leaf flour (moringa oleifera) as substitution of tapioca flour to the elasticity and acceptance power of cilok. Methods : This research uses complete precipitate with 4 treatments and 2 remidials. The substitution of kelor leaf flour which is used are 0%, 5%, 7,5%, and 10%. The data of acceptance power analyzing uses statistic one way anova and then continued with DMRT (Duncan Multiple Range Test) is 95%. Results : It has a substitution influence of kelor leaf flour in the tapioca flour for cilok's color. Conclusion : It has a substitution effect of kelor leaf flour to the elasticity of cilok. It has influence increase in the aceptancepower of cilok. Advice : Taking from the result of the research it suggests that the use of kelor leaf flour substitution is 5% for making cilok.